Pengaruh Perbandingan Kacang Merah dan Tepung Tapioka dalam Pembuatan Keripik Tempe Kacang Merah (Phaseolus Vulgaris L.) terhadap Daya Terima Konsumen dan Sifat - Pedro Reynald Ananta; I Gusti Ayu Ngurah Singamurni; Ridawati (Jurnal Sains Boga, 2022)
Red bean (Phaseolus vulgaris L.) is a cowpea of ​​the Fabaceae family which has the same potential and properties as soybeans to be processed into tempeh chips. Tempe chips are processed tempeh with tapioca starch as a mixing ingredient during fermentation for 36 hours at a temperature of 25-30 ℃ then thinly sliced ​​1.5 cm thick and fried in palm oil at 180 ℃ using the deep frying method. This study aims to see how much consumer acceptance is in terms of color, bean density, shape, aroma, crispness and taste and the physical properties of red bean tempeh chips which include thickness, diameter and swelling power with three ratios of red beans and tapioca starch of (1 :1, 1:1/2 and 1:1/3). Red bean tempeh chips with a ratio of red beans and tapioca starch of 1:1/2 gave the best consumer acceptance rating compared to other comparisons with an average value of 4.6 and physical characteristics of red bean tempeh chips with a ratio of red beans and tapioca starch of 1 :1 is the best compared to other comparisons with an average swelling value of 41.766 and an average diameter swelling value of 0.0308.